Subclinical/overt hypothyroidism may be associated with diminished ovarian reserve in infertile women independent of thyroid autoimmunity - Zhang, Hongzhan; Qiu, Han; Liu, Zhiqiang; Wu, Yulian; Liu, Wei; Huang, Chunyu (Frontiers in Endocrinology, 2024)
Objective:To investigate the association between thyroid dysfunction or thyroid autoimmunity (TAI) and diminished ovarian reserve (DOR).A total of 2867 women undergoing their first in-vitro fertilization (IVF) cycle at Shenzhen Zhongshan Obstetrics & Gynecology Hospital between January 1, 2013 and June 30, 2021,were enrolled in this study.The participants had documented thyroid and ovarian reserve metrics.They were categorized into three groups based on their thyroid function:normal thyroid function (N=2540), subclinical/overt hypothyroidism (SCH/OH) (N=290),and subclinical/overt hyperthyroidism (N=37).Anti-Mullerian hormone (AMH) and antral follicle count (AFC) were assessed and collected. Women with AMH<1.2ng/mL and AFC<5 were diagnosed with DOR.Basic characteristics and ovarian reserve-related parameters were compared among the three groups.The association between thyroid function and ovarian reserve function was further analyzed using logistical regression analyses.In addition,the euthyroid population was stratified using a thyroid-stimulating hormone (TSH) threshold of 2.5µIU/mL,and the ovarian reserve-related parameters were compared among women with low-normal TSH (TSH<2.5µIU/mL),high-normal TSH (2.5µIU/mL≤TSH≤4.2µIU/mL) and SCH/OH.Women with SCH/OH had lower AMH levels (2.79ng/mL vs. 3.41 ng/mL,P<0.001) and a significantly higher prevalence of AMH level <1.2ng/mL (17.2% vs.12.1%, P=0.015) compared to those with normal thyroid function. The prevalence of DOR was also higher among women with SCH/OH (10.0% vs. 6.5%, P=0.036). There were no significant differences in ovarian reserve between women with normal thyroid function and those with subclinical/overt hyperthyroidism.Logistic regression analyses showed that the odds ratio (OR) of women with SCH/OH suffering from DOR was 1.666 (95% CI: 1.079-2.572) compared to those with normal thyroid function, after adjusting for TAI status and basic clinical characteristics.When the euthyroid group was stratified according to TSH levels, women with SCH/OH showed significantly lower AMH levels compared to women with low-normal TSH (2.79ng/mL vs. 3.44ng/mL, P<0.001) and a significantly higher prevalence of DOR (10.0% vs. 6.0%, P=0.010).Logistic regression analyses showed that the women with SCH/OH had an increased prevalence of DOR(OR: 1.819,95% CI: 1.158-2.858) compared to those with low-normal TSH, after adjusting for TAI status and basic clinical characteristics.However, the OR for DOR among women with high-normal TSH was not significantly elevated compared to those with low-normal TSH(OR: 1.310,95% CI: 0.936-1.832).SCH/OH may be associated with DOR, irrespective of TAI status.